Effect of Activator Composition on the Setting Time and Compressive Srength Of Fly Ash–Lime-Based Geopolymer Paste - Ramadhan, B.R.; Lonardya, C.J.; Adam, A.A.; Akifa, S.N.; Wahidin, S.N.; Payung, F.R. (REKONSTRUKSI TADULAKO: Civil Engineering Journal on Research and Development, 2025)
This study aims to investigate the optimal composition of geopolymer paste based on fly ash and lime to achieve ambient temperature hardening, ideal setting time, and high compressive strength. The primary materials used include Class F fly ash from the Mpanau coal-fired power plant and hydrated lime (calcium hydroxide) at 5% of the fly ash weight. The activators employed were Sodium Silicate (Na2SiO3) and Sodium Hydroxide (NaOH), with Na2O dosage variations of 7.5%, 10%, and 12.5%, and activator modulus (SiO2/Na2O ratio) variations of 0.75, 1.00, and 1.25. The specimens were cylindrical with a diameter of 25 mm and a height of 50 mm, and compressive strength tests were conducted at 3, 7, 14, and 28 days. The results showed that the optimum setting time was achieved at a Na2O dosage of 7.5% with an activator modulus of 0.75 and 1.00, yielding setting times of 88.67 and 60.94 minutes, respectively. The highest compressive strength was recorded at a Na2O dosage of 10% with an activator modulus of 1.25, reaching 29.76 MPa at 28 days. These findings suggest that the composition of the alkaline activator significantly influences the early-age properties and mechanical performance of fly ash–lime-based geopolymer paste